ANALISIS PENILAIAN PERSEDIAAN PADA APOTEK DELFITA FARMA DI SAMARINDA - SITI NOOR SELMA ANGGRAINI; HAMID BONE; IRWANSYAH - (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2016)
The purpose of this study was to determine the fairness of the presentation of the value of inventory in financial statements Pharmacies Delfita Farma in Samarinda and analyzing records inventory Pharmacies Delfita Farma using the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) to determine differences in the value of ending inventory. The analysis tool used is the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP). Based on analysis tools that have been used got the final result of inventory is Rp 7,124,897.00 with no difference in the unit. Based on research, the analysis shows that the value of ending inventory by Pharmacies Delfita Farma is different from the value of ending inventory valuation using LIFO (Last In, Firts Out) method. final inventory's Alloris Tablet Rp 237,991.00 and Rp 238,924.00, Eflagen 50 mg of Rp 301,340.00 and Rp 301,500.00, Sanexon 4 mg of Rp 333,500.00 and Rp 339,625.00 and the final inventory Anbacim 500 mg no difference. Final inventory according to calculations Pharmacies Delfita Farma is Rp 7,124,897.00 while the calculation according to the author is Rp 7,132,115.00 resulting in a difference in the value of inventories amounting to Rp 7128.00. Therefore, the authors suggest Pharmacies Delfita Farma can improve assessment methods inventory so it can be in accordance with Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) Chapter 11 Inventories are just using assessment LIFO (Last In, Firts Out) methods and Weighted average or average.Keywords: Assessment Inventory, FIFO